Cu2+-RGDFRGDS: exploring the mechanism and high efficacy of the nanoparticle in antithrombotic therapy - Wu J (Dove Medical Press, 2015)
Jianhui Wu,1 Yuji Wang,1 Yaonan Wang,1 Ming Zhao,1,2 Xiaoyi Zhang,1 Lin Gui,1 Shurui Zhao,1 Haimei Zhu,1 Jinghua Zhao,1 Shiqi Peng11Beijing Area Major Laboratory of Peptide and Small Molecular Drugs, Engineering Research Center of Endogenous Prophylactic of Ministry of Education of China, Beijing Laboratory of Biomedical Materials, College of Pharmaceutical Sciences, Capital Medical University, Beijing, People’s Republic of China; 2Faculty of Biomedical Science and Environmental Biology, Kaohsiung Medical University, Kaohsiung, TaiwanAbstract: Thrombosis disease has been the leading cause of morbidity and mortality worldwide. In the discovery of antithrombotic agents, three complexes of Cu2+ and repetitive arginine-glycine-aspartic acid (RGD) sequences, Cu(II)-Arg-Gly-Asp-Ser-Arg-Gly-Asp-Ser (Cu[II]-4a), Cu(II)-Arg-Gly-Asp-Val-Arg-Gly-Asp-Val (Cu[II]-4b), and Cu(II)-Arg-Gly-Asp-Phe-Arg-Gly-Asp-Phe (Cu[II]-4c), were previously reported, of which Cu(II)-4a and Cu(II)-4c possessed the highest in vitro and in vivo activity, respectively. Transmission electron microscopy (TEM) images visualized that Cu(II)-4a and Cu(II)-4c formed nanoaggregates and nanoparticles, respectively. However, the details of the formation of the nanospecies complexes and of the mechanism for inhibiting thrombosis remain to be clarified. For this purpose, this study designed a novel complex of Cu(II) and the RGD octapeptide, Arg-Gly-Asp-Phe-Arg-Gly-Asp-Ser (RGDFRGDS), consisting of Arg-Gly-Asp-Phe of Cu(II)-4c and Arg-Gly-Asp-Ser of Cu(II)-4a, to colligate their biological and nanostructural benefits. In contrast with Cu(II)-4a, -4b, and -4c, Cu(II)-RGDFRGDS (Cu2+-FS) had high antiplatelet and antithrombotic activities, with the formed nanoparticles having a porous surface. Additionally, this paper evidenced the dimer had the basic structural unit of Cu2+-FS in water, theoretically simulated the formation of Cu2+-FS nanoparticles, and identified that Cu2+-FS activity in decreasing glycoprotein IIb/IIIa, P-selectin, and IL-8 was responsible for the antithrombotic action. Finally, adherence onto the surface and entry into the cytoplasm were considered the steps of a two-step model for the blocking of platelet activation by Cu2+-FS nanoparticles. Findings indicated that the antiplatelet aggregation activity of Cu2+-FS was 10–52 times higher than that of RGDFRGDS, while the effective dose for antithrombotic action was 5,000 times lower than that of RGDFRGDS.Keywords: GPIIb/IIIa, IL-8, TEM, AFM, SEM, nanomedicine